2021
DOI: 10.1111/gcb.15564
|View full text |Cite
|
Sign up to set email alerts
|

Reduced photosynthetic thermal acclimation capacity under elevated ozone in poplar (Populus tremula) saplings

Abstract: The sensitivity of photosynthesis to temperature has been identified as a key uncertainty for projecting the magnitude of the terrestrial carbon cycle response to future climate change. Although thermal acclimation of photosynthesis under rising temperature has been reported in many tree species, whether tropospheric ozone (O3) affects the acclimation capacity remains unknown. In this study, temperature responses of photosynthesis (light‐saturated rate of photosynthesis (Asat), maximum rates of RuBP carboxylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 91 publications
0
9
0
Order By: Relevance
“…However, once the optimal temperature threshold of photosynthesis is exceeded, exposure to heat stress could cause the separation of the light‐harvesting complexes from the photosystem II (PSII) reaction center or the denaturation of proteins (Gounaris et al ., 1984 ; Yamane et al ., 1997 ). The consequences are reduced A sat, V c max, and J max with high temperatures (Medlyn et al ., 2002 ; Dai et al ., 2021 ; Dusenge et al ., 2021 ), a reduction of the maximum photochemical efficiency ( F v / F m ) and decreasing chlorophyll (Chl) concentrations. Variation in these responses largely depends on the species' temperature range.…”
Section: Introductionmentioning
confidence: 99%
“…However, once the optimal temperature threshold of photosynthesis is exceeded, exposure to heat stress could cause the separation of the light‐harvesting complexes from the photosystem II (PSII) reaction center or the denaturation of proteins (Gounaris et al ., 1984 ; Yamane et al ., 1997 ). The consequences are reduced A sat, V c max, and J max with high temperatures (Medlyn et al ., 2002 ; Dai et al ., 2021 ; Dusenge et al ., 2021 ), a reduction of the maximum photochemical efficiency ( F v / F m ) and decreasing chlorophyll (Chl) concentrations. Variation in these responses largely depends on the species' temperature range.…”
Section: Introductionmentioning
confidence: 99%
“…Our observations directly support H1 and are largely consistent with the results of previous studies on temperature acclimation in poplar. 20,50,51 Hybrid poplar clones (P. maximowiczii x P. nigra and P. maximowiczii x P. balsamifera) 50 and P. tremula saplings 51 grown at an elevated temperature showed an increase in T Opt and acclimation of R d . 50 Equally, P. euramericana saplings at the same growth temperatures used in the present study (HGT, 35 °C and LGT, 25 °C) showed a considerable downward acclimation of P n , g s , and both dark (R d ) and light respiration (R l ).…”
Section: Discussionmentioning
confidence: 98%
“…A sat for M. breviflora in CBMF and MEBF were mainly reduced by the direct effect of higher T soil , subsequently leading to lower water uptake from the soil, and lower g s . Higher T air directly increased g s of S. rehderianum in MEBF, leading to increasing A sat and growth (Dai et al, 2021). However, growth of S. rehderianum in CBMF was lower due to translocation warming.…”
Section: Direct Effects Of Higher T Air and T Soil On Plant Physiolog...mentioning
confidence: 94%